Glycerol–Choline Chloride Natural Deep Eutectic Solvent: A GreenAlternative for Caffeine Extraction - Ritika; Anupma Sharma; Neha; Saurav kumar (RSYN Proceedings, 2025)
Caffeine (C₈H₁₀N₄O₂) is a major bioactive compound present in tea leaves, coffee beans, and chocolate[1]. Caffeine acts a stimulant to our central nervous system and mostly used in food and medicinal products[2]. This has led to increasing interest in developing more environmentally sustainable extraction methods. This study involved the synthesis and application of a natural deep eutectic solvent (NADES) composed of glycerol (hydrogen bond donor) and choline chloride (hydrogen bond acceptor) for the extraction of caffeine from tea leaves. Fourier-transform infrared spectroscopy (FTIR) was employed to examine the structural and physicochemical characteristics of the synthesised NADES. The pH, viscosity, conductivity, and thermal stability of the NADES were carefully evaluated. Extraction studies were conducted at varying concentrations of NADES (25–100%) to optimise caffeine yield. Ultra-high-performance liquid chromatography (UHPLC) and the Folin–Ciocalteu technique to quantify caffeine and total polyphenol content (TPC) respectively. Distinct shifts in key absorption bands in FTIR of NADES prove the molecular interactions, mainly hydrogen bonding, between choline chloride and glycerol. The glycerol–choline chloride NADES demonstrated significantly enhanced extraction efficiency, yielding up to the amount of caffeine compared to conventional solvent systems. This suggests that this NADES combination may serve as an effective greener method for extracting caffeine from tea without using any harmful solvent.